The Development of electronic group counseling (EGC) software to optimize counseling services in Indonesia - Eddy Wibowo, Mungin; Mahfud, Ashari; Khiyarusoleh, Ujang (KONSELOR, 2023)
Counseling services are currently an increasing need in society. This is proof that modern life makes people vulnerable to their psychological well-being. However, current counseling services still have limitations such as distance and time with clients. Therefore, the development of electronic group counseling (EGC) software was the reason for its development to optimize services to clients. EGC development was carried out by adopting the Borg & Gall model. These stages include; 1) literature review, 2) product preparation, 3) first stage trial, 4) product revision, 5) second stage trial, 6) final product revision. The trial was carried out involving 25 guidance and counseling teachers, as well as 500 high school level students spread across Central Java province. The selection of subjects in this research was carried out using cluster sampling techniques. The data collected relates to teachers' experiences in using this application in implementing counseling services. Meanwhile, data from students was collected to see students' experiences in using counseling services with the EGC application. Data collection was carried out using the counseling service satisfaction instrument with EGC which had previously been developed by researchers. The results obtained will then be described quantitatively. The results of this development produce EGC software that is ready to use. This software makes it easier for counselors to plan meetings with clients, assess clients' conditions, meet virtually with clients, and create counseling reports. This software complements the findings of cybercounseling products which are currently being developed in Indonesia. Supporting technological advances, counseling comes with various innovations that are able to create more effective and efficient services for clients.